STUDI FENOMENOLOGI PERILAKU PERUNDUNGAN DAN DAMPAKNYA TERHADAP KESEHATAN MENTAL SISWA DI YOGYAKARTA - Murni, Sri; Perianto, Eko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying is one of the problems that frequently occurs in the school environment and can have negative impacts on students' mental health. This behavior not only affects the emotional condition of the victims but also influences their social relationships and learning motivation at school. This study aims to understand the subjective experiences of students who become victims of bullying and to identify the impact of bullying on the mental health of seventh-grade students at SMP Negeri 10 Yogyakarta. This research employed a qualitative approach using a phenomenological method. Data were collected through in-depth interviews, observations, and documentation involving seven students who were victims of bullying, one school counselor, and two homeroom teachers. The validity of the data was tested through source, method, and time triangulation. The results of the study indicate that students experience various forms of bullying, such as teasing, derogatory nicknames, and social exclusion. These experiences lead to psychological impacts including feelings of anxiety, sadness, withdrawal from social environments, decreased self-confidence, and reduced learning motivation. These findings show that bullying has a significant influence on students' psychological well-being, highlighting the importance of active involvement from schools in preventing and addressing bullying. Keywords: bullying, mental health, junior high school students, phenomenology.